Allais at the Horse Race: Testing models of ambiguity aversion - Florian Schneider; Martin Schonger (University of Zurich, Department of Economics, 2015)
Most models of ambiguity aversion satisfy Anscombe-Aumann's Monotonicity axiom. This paper proposes a test of Monotonicity, the Allais Horse Race. It is an adaptation of the Allais paradox to a setting with both subjective and objective uncertainty. Viewed as a thought experiment, the Allais Horse Race allows for introspective assessment of Monotonicity. Implementing it as an incentivized experiment, we find that the modal choice of subjects violates Monotonicity in a specific, intuitive way. Overall, we find that models of ambiguity aversion that satisfy Monotonicity cannot describe the behavior of about half of all subjects.
Keywords: D81; 330; ambiguity aversion; monotonicity; Anscombe-Aumann; Allais paradox; experiments